Expert performance in action anticipation: visual search behavior in volleyball spiking defense from different viewing perspectives - Zhu, R.; Zou, D.; Wang, K.; Cao, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction Volleyball spiking requires defenders to possess exceptional anticipatory skills. Athletes` visual search skills, enable them to execute appropriate responses, thereby facilitating effective anticipation. Behavioral studies have consistently demonstrated that athletes tend to exhibit superior perceptual-cognitive abilities, particularly in sports-specific contexts. In addition to subjective methods such as verbal reports, eye-tracking devices can be used as scientifically objective instruments to measure expert athletes` visual search skills. However, Previous volleyball defense video eye-tracking studies used fixed or off-court perspectives, failing to replicate real-world environments. The present study investigated visual search behaviors in spike defense anticipation from different back-row viewing perspectives, including one baseline off-court perspective and three on-court perspectives. Methods We examined the spiking anticipation ability and visual search behavior of 14 competitive elite, 13 semi-elite, and 11 novice players using the Tobii Pro eye-tracking device. We let them see the spiking video and instructed them to press a key to anticipate the landing location of the ball. For video production, We captured spiking videos from three on-court perspectives using GoPro cameras mounted on the back-row defenders heads, closely replicating real game scenarios. For comparison, we recorded baseline videos using a fixed camera. For Areas of interest, we divided videos into 2 phases: pre-spike and spiking phase. We used repeated ANOVA and subsequent Bonferroni post hoc analyses in SPSS to explore the differential effects between groups and perspectives. Results The repeated measures ANOVA with factors 3 (group) × 4 (perspective) demonstrated a notable interaction effect on RA (F(6,68) = 2.204, p = 0.050, *2 = 0.163). The CE (58.5% ± 3.3%) and SE (56.3% ± 5.0%) groups were significantly superior to the novice group (49.9% ± 4.8%). Competitive elite players used fewer fixations(t=6.241, p< 0.001, *2 = 0.918). Discussion Elites are more skilled than novices in utilizing early visual cues to anticipate opponents` actions. Elites superior performance was related to stable visual search patterns (fewer fixations and longer duration). CEs are likely more adept than SEs and novices at utilizing their peripheral vision for global perception. From the baseline perspective, the participants primarily utilized global perception and peripheral vision, focusing more on the setter zone or the spiker`s trunk. Conversely, from the on-court perspective, they employed more fixations, focusing more intensely on the spiker`s detailed movements.